Experimental Investigation of the Thermal Decomposition Pathways and Kinetics of TATB by Isotopic Substitution. Issue 9 (8th June 2021) - Koroglu, Batikan; Crowhurst, Jonathan C.; Kahl, Evan M.; Moore, Jason S.; Racoveanu, Ana; Mason, Harris E.; Weisz, David G.; Reynolds, John G.; Burnham, Alan K.
Abstract: Real‐time measurements of the product gases arising from the thermal decomposition of triamino‐trinitro benzene (TATB), its deuterated analogue, and plastically bonded TATB (LX‐17) are presented in this study. Gas‐phase decomposition products are identified by IR absorption spectroscopy. The frequency shifts in rovibrational spectra due to isotopic substitution and the change in rate of formation of decomposition products due to the kinetic‐isotope‐effect (KIE) help elucidate the decomposition pathways. The formation of H2 O precedes other molecules (e. g., HCN, HNCO) during decomposition. After the concentrations of HCN and HNCO molecules reach a peak, their amounts gradually decrease. The concentrations of the other decomposition products (e. g., NH3 and CO2 ) rapidly rise after an induction period, which is attributed to the presence of autocatalytic reactions. The trends of chemical evolution are similar for all the samples, but their kinetic behaviors are different. This indicates the rates of consistent pathways are changed during thermal decomposition. The kinetics of deuterated TATB decomposition is slower than that of unsubstituted TATB due to the KIE (kH /kD ∼1.41). The rate of LX‐17 decomposition is slightly lower than unsubstituted TATB (kTATB /kLX‐17 ∼1.15). The KIE is more pronounced during the early stage of decomposition, which is attributed to the first steps of TATB decomposition involving water formation (i. e., H vs D transfer). The KIE slows down the formation of all gases, including those lacking hydrogen (e. g., CO2 ). These results suggest the TATB thermal decomposition mechanism might involve a series of pathways rather than a set of independent and parallel reactions. Abstract :